1991
DOI: 10.1111/j.1432-1033.1991.tb15842.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fish oil and corn oil on lipid metabolism and apolipoprotein gene expression by rat liver

Abstract: A 3-week fish oil diet induced in weanling rats a decrease in plasma lipids and liver triacylglycerol, and an increase in insulinemia, compared to a corn oil diet. At the same time, plasma apolipoprotein (apo) A-I was slightly lower and plasma heavy apo Bjlight apo B ratio was higher in fish-oil-fed than in corn-oil-fed rats. Hepatocytes obtained from fish-oil-fed and corn-oil-fed rats were used to examine how fish oil affects lipid and apolipoprotein synthesis and secretion. Primary culture of hepatocytes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 60 publications
2
32
1
Order By: Relevance
“…The authors observed that the inhibition of the n-6 pathways occurred at low (0. (Roach ef al, 1987a (Roach et al, 1987a (Harris et al, 1983;Balasubramaniam et al, 1985;Huang et al, 1986;Roach et al, 1987a;Chautan et al, 1990;Ribeiro et al, 1991;Otto et al, 1991 It It is unlikely that the small excess of saturated fatty acids fed to the SM group could attenuate the hypotriglyceridemic effect of long-chain n-3 PUFA. Indeed saturated fatty acids accounted for only 2.4 and 1.6% of total energy in SM and SF diets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that the inhibition of the n-6 pathways occurred at low (0. (Roach ef al, 1987a (Roach et al, 1987a (Harris et al, 1983;Balasubramaniam et al, 1985;Huang et al, 1986;Roach et al, 1987a;Chautan et al, 1990;Ribeiro et al, 1991;Otto et al, 1991 It It is unlikely that the small excess of saturated fatty acids fed to the SM group could attenuate the hypotriglyceridemic effect of long-chain n-3 PUFA. Indeed saturated fatty acids accounted for only 2.4 and 1.6% of total energy in SM and SF diets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These authors, however, did not measure apo A-I mRNA steadystate levels in whole liver. Furthermore, primary hepatocytes from fish oil and control rats were both supplemented with oleic acid in their study [49], which may up-regulate apo A-I expression [50]. It is, therefore, conceivable that the culture conditions used in their study conceal the effects of the fish oil diet on hepatic apo A-I gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports on how fish oil affects fatty acid metabolism in mammals (Ribeiro et al, 1991;Kim et al, 1999;Yu et al, 2010), but few have focused on birds. Moreover, the effects of dietary C. butyricum on the expression of genes linked to fatty acid metabolism have not been examined in chickens.…”
Section: Introductionmentioning
confidence: 99%